The Arbitrability of Corruption: Is it Possible to Apply "Clean Hands Doctrine" in Arbitration in Public Procurement? - Espinoza Quiñones, Sandro (2015)
The arbitration proceeding is characterized for being an efficient, impartial, and above all a transparent mechanism, wherefore various private and public entities have aimed to it in order to solve their patrimonial controversies. Nevertheless, there is a sector within the doctrine that maintains that, on the assumption that the matter to arbitrate comes from legal relationships marked by corruption, the arbitration court should declare the unarbitrability of the matter, since it would violate the public order.The present paper will broach the impact of the entitled «Clean Hands Doctrine» on certain Law branches, its origins on the worldwide legal systems, the relation of it with other legal entities on which it is based on, and we will discuss international legal precedents on the matter, as well as the possible application of this doctrine to arbitration proceedings on a local context and in public procurements matter.